THE PDCA CYCLE IN THE CONTEXT OF REDUCING PSYCHO-EMOTIONAL TENSION IN THE WORKPLACE - Danova, K.; Malysheva, V.; Kolybelnikova, L.; Lohvinkov, S. (Municipal economy of cities. Series: «Economy science», 2023)
The necessity to ensure work safety begins with an understanding of the risks that exist in the enterprise and can lead to injury, deterioration of the health of employees, and accidents. Such risks may include physical, chemical, biological, and psychosocial hazards. The negative consequences of the psycho-emotional tension of employees consist of a decrease in the level of concentration of attention, increased fatigue, deterioration in the perception and memorisation of information, and a decrease in work efficiency. Some serious consequences of the excessive psycho-emotional tension of the employee are an increasing risk of accidents during the performance of work tasks, an increased time absence at work due to illness, a decrease in the quality of the work performed, loss of motivation, and others. The article analyses the possibilities of using the PDCA Cycle methodology to eliminate psycho-emotional tension in the workplace. We revealed the dangerous psycho-emotional factors in the workplace and provided examples of using each stage of the PDCA Cycle to reduce their impact on employees and ensure safe indicators of working conditions. The PDCA cycle can be implemented as a mean of improving the management and normalisation of safe work conditions, using the main idea of the model—the continuous improvement of safety indicators, through a step-by-step cycle: planning, execution, inspection, and action. The Deming circle allows us to systematically identify, analyse and solve problems related to psycho-emotional tension in the workplace, as well as to constantly improve processes in order to prevent the emergence of new stress factors. The application of this approach will provide effective control over psycho-emotional risks, reduce their impact on the health and safety of employees, improve overall production productivity, and is also a valuable tool for evaluating the effectiveness of the safety management system at the enterprise and for making decisions on improving working conditions.